Teaching world history as mystery - Zevin, Jack; Gerwin, David (New York Routledge, 2011)
Presents a philosophy, methodology, and examples for world history instruction based on inquiry and problem-solving methods that promote reasoning and judgment and restore a sense of imagination and participation to classroom learning.
Teaching world history as mystery -- Looking at world history anew -- Stones that speak : of megaliths and monoliths -- Rome lasts! A mystery of durability and power -- Mythlabeled? Creating the Crusades -- The possibilities for pizza : a search for origins -- Incas and Spaniards -- Secrets of secret societies -- Where are the women in world history? -- Conclusion.
Keywords: History -- Study and teaching -- United States